2018
DOI: 10.1080/2162402x.2018.1498285
|View full text |Cite
|
Sign up to set email alerts
|

Systemic autophagy in the therapeutic response to anthracycline-based chemotherapy

Abstract: The success of chemotherapy largely depends on the anticancer immune response triggered by tumor cells that succumb to immunogenic cell death (ICD). One of the hallmarks of ICD is premortem autophagy that facilitates the release of adenosine triphosphate from dying cancer cells and acts as a chemoattractant for dendritic cell precursors. Here, we show that the immune response induced by inoculation of cancer cells undergoing ICD in response to the anthracycline mitoxantrone (MTX) can be improved by a short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
1
14
0
2
Order By: Relevance
“…It has been claimed by several independent groups that α-ketoglutarate inhibits autophagy [2125,33]. However, the contrary has been reported as well, namely, that α-ketoglutarate would induce autophagy [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been claimed by several independent groups that α-ketoglutarate inhibits autophagy [2125,33]. However, the contrary has been reported as well, namely, that α-ketoglutarate would induce autophagy [26].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several papers have been published that claim contradictory effects of α-ketoglutarate on autophagy. Several works indicate that addition of the α-ketoglutarate precursor dimethyl α-ketoglutarate (DMKG) to human cell cultures or its intraperitoneal injection into mice effectively inhibits autophagy through an anaplerosis-dependent increase in acetyl-CoA (AcCoA) levels, thus, increasing the acetylation of cytoplasmic proteins [2125]. In contrast, another paper claims that addition of another α-ketoglutarate precursor, octyl α-ketoglutarate (O-KG) induces autophagy both in human cells and in Caenorhabditis elegans , because it inhibits the mitochondrial ATP synthase as well as MTORC1 [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Up till now, contradictory effects of αKG on autophagy have been reported. Several studies demonstrate that addition of the αKG to mammalian cells or its administration into mice effectively inhibits autophagy [41][42][43][44] . In sharp contrast, Chin et al have shown that αKG inhibits mTORC1 and the mitochondrial ATP synthase and therefore induces autophagy both in mammalian cells and in Caenorhabditis elegans 26,45 .…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] ICD inducers are widely used in cancer therapy and are still undergoing clinical evaluation. 20,21 One of the premortem responses that is elicited by ICDinducing chemotherapeutics is autophagy, 22 which in turn facilitates the release of adenosine triphosphate (ATP) from dying cancer cells. 23 Extracellular ATP acts on purinergic receptors to attract DC precursors into the tumor bed and to facilitate their local activation.…”
Section: Introductionmentioning
confidence: 99%